Pengaruh Bekerja Dari Rumah Dan Efikasi Diri Terhadap Kinerja Guru Dimasa Pandemi Covid -19 (Studi Pada Guru SMAN 01 Singosari) - Siti Nur Khofifah; Siti Asiyah; Alfian Budi Primanto (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This study aims to determine the effect of working from home, self-confidence and work spirit on teacher performance (at SMAN 01 SINGOSARI teachers). The type of research used is quantitative method. Collecting data using a questionnaire from the sample used as many as 54 respondents. The data analysis technique used is multiple linear regression analysisThe results of this study indicate that working from home and self-efficacy on teacher performance (at SMAN 01 SINGOSARI teachers) have a simultaneous effect. Working from home has a positive and significant effect on teacher performance, which means that working from home has a more efficient effect on working without having to pay for transportation to school. Self-efficacy has a positive and significant effect on teacher performance, which means that high and good confidence in the abilities of the teacher's performance results in increased teacher performance. Keywords: Working From Home and Self-Efficacy Against Teacher Performance.